Diferentefects of pulsed X-rays in MOLT-4 cel line and human peripheral blod lymphocytes - S. A. Vasilyev; A. A. Belenko; O. P. Kutenkov; M. A. Bolshakov; I. N. Lebedev; V. V. Rostov (Сибирский онкологический журнал, 2016)
Effects of ionizing radiation registered in cells after low dose irradiation are still poorly understood. Thus, the aim of this study was to analyze effects of pulsed X-rays on level of radiation-induced DNA double-strand breaks and their repair kinetics in cancer and normalhuman cells in vitro. Analysis of radiation-induced γH2AX and 53BP1 repair foci in MOLT-4 cells with lymphoblastic origin was used for assessment of DNA double-strand breaks (DSB) in these cells. Number of residual radiation-induced γH2AX and 53BP1 foci at 18 hafter irradiation depended on frequency of X-ray pulses: at 8 pulses per second effect was highest in MOLT-4 cells and lowest in peripheral blood lymphocytes. It suggests that pulsed X-rays with various frequencies could be used for target influence on cancer cells being lessdeleterious for normal human cells.